Lepidiumuridine A: A New Natural Uridine Derivative as a Phytoestrogen Isolated from the Seeds of Lepidium apetalum Willd. (4th September 2018) - Li, Meng; Zeng, Mengnan; Zhang, Zhi-guang; Zhang, Beibei; Zhang, Jingke; Zheng, Xiaoke; Feng, Weisheng
Abstract : There has been great interest in phytoestrogens, which are polyhydric compounds that are derived from plants and have a structure similar to that of the mammalian steroid hormone 17 β -estradiol. The present study examined the estrogenic effects of a new natural uridine derivative, lepidiumuridine A (LA), that was isolated from the seeds of Lepidium apetalum . The structure was clarified and determined via analysis of extensive spectroscopic data interpretation. The activity of LA was investigated by measuring the levels of estradiol (E2), luteinizing hormone (LH), follicle stimulating hormone (FSH), and the uterus growth in mice. The proliferation experiment of MCF-7 breast cancer cells was also conducted. Western blot, in-cell western, and antagonist assays with methyl piperidino-pyrazole (MPP) were used for exploring the mechanism of the effects of LA. The results showed that LA elevated the uterine coefficient, the levels of E2, and FSH significantly. In addition, LA significantly elevated ER α expression in the uterus and MCF-7 cells. MPP inhibited the proliferation of LA-stimulated MCF-7 cell and ER α expression in MCF-7 cells. Taken together, LA had an estrogen-like effect, which was mainly mediated by the estrogen receptor ER α .